An empirical study on job burnout among university counselors and the improvement of occupational happiness - Liang, Qing-Qing; Yin, Fang (Frontiers in Psychology, 2025)
University counselors undertake a significant amount of repetitive and trivial work. The high-pressure, high-load nature of their duties gradually erodes their enthusiasm and consumes considerable psychological resources, leading to a higher-than-average level of job burnout among university counselors. The article examines the practical work of university counselors, analyzing and validating the moderating role of emotional intelligence in the relationship between emotional labor and job burnout. In September 2023, a survey was conducted involving 520 university counselors from 25 different types of universities, located across six provinces in eastern, central, and western China. Using the General Information Questionnaire for University Teachers, the Emotional Labor Scale, the Emotional Intelligence Scale, and the Job Burnout Scale, this empirical study investigated job burnout and mental health among counselors. The study aimed to assess the level of job burnout among university counselors and to propose suggestions for enhancing their occupational happiness. The results indicate that burnout among university counselors increases with age, with counselors aged 26–30 experiencing the highest levels of depersonalization and burnout. Furthermore, it has been observed that emotional intelligence tends to escalate with advanced educational attainment. Counselors scored higher on the dimensions of deep acting and genuine emotional expression compared to surface acting. It is recommended to address burnout from both individual and organizational dimensions, with particular focus on counselors aged 26–30. Implementing targeted training programs to enhance emotional intelligence can help reduce job burnout. Efforts should be made to transform burnout into occupational attachment, achieving harmony between the individual and their profession.